"Free your heels - free your mind" : telemark skiing - a lifestyle sport in Finland - Haapanen, Eeva (2019)
Telemark skiing can be called the ancestor of downhill skiing as its history started almost 150 years ago in Norway. The almost forgotten skiing style had a new coming in the 1970s in the United States and gained popularity around the world in the 1990s. In Finland the number of telemark skiers is estimated to be approximately four percent of all the downhill sport enthusiasts. Even though telemark seems to be slightly growing lately it is still a marginal sport, unknown to many. There is not much academic knowledge about telemark skiing in Finland and it has not been studied sociologically. The main purpose of this research is to find out the socioeconomic profiles of the telemark skiers in Finland and what are the reasons to participate in the sport. The skiers’ preferences, forms of skiing, physical activity and expenditure in telemark skiing are also studied. Answers are given also to telemark skiers’ motivation to be part of a club and how skiers would develop the sport in Finland. The data was collected by a questionnaire that was sent to a Facebook group Telemark Suomi Finland FB in spring 2015. The group has almost a 1000 members, but the size of the group changes all the time, mainly growing. Approximately 40 percent of the group members answered the questionnaire. These responses were analysed with both quantitative and qualitative methods. IBM SPSS Statistics was used to analyse the numerical data of closed questions and qualitative methods to analyse the open-ended questions. The research was guided by a hermeneutic approach, in other words with an interpretation, which aims at understanding a phenomenon by revealing hidden meanings. The gained information helps to understand and explain telemark skiing and its meaning for the telemarkers in Finland. The results revealed that a typical telemark skier in Finland is 38 years old and highly educated. Approximately 38 percent of the skiers were women and 62 percent men. An intriguing fact is that female telemark skiers were on average better educated and earned more than men. People ski telemark mostly because it is challenging, versatile and fun and because the sport has a relaxed image. The results prove that ‘free your heels – free your mind’ can be a suitable marketing slogan for telemark skiing. The results of this master’s thesis will at best contribute to the development of different clubs and Telemark Suomi Finland Facebook -community. The data provides useful information for different equipment brands, shops and ski resorts for their marketing purposes. This research also gives interesting information about adults’ motivational factors to participate in lifestyle sports, their skiing preferences and how much time and money they spend on their hobby. The results will hopefully also facilitate and lead to further studies on the subject.